Serum pentraxin-3 levels in acute stroke: No association with stroke prognosis. Issue 2 (December 2015) - Ceylan, Mustafa; Yalcin, Ahmet; Bayraktutan, O. Faruk; Atis, Omer; Acar, Ethem
Abstract: Background: Stroke is the leading cause of serious disability. Estimating severity of the disease and early risk assessment is crucial. Several studies have been carried on and several biomarkers have been proposed in the literature for risk assessment and to estimate the stroke prognosis. In this study we assessed the association of predictors such as patient age, gender, stroke volume and NIHS scores on prognosis of stroke event. We investigated whether the serum pentraxin-3 levels are linked with stroke prognosis. Methods: Forty-four stroke patients without cardiovascular risk factors were included in this study. Initial NIHS scores, stroke volumes, serum pentraxin-3 levels and the data regarding the risk factors were collected in the first and seventh days of event. Association of predictors with final NIHS scores were investigated using multivariate regression model. Results: Initial NIHS score, initial and final stroke volumes were independently associated with final NIHS score whereas serum pentraxin-3 levels, whether acquired at the first or seventh day of stroke, were not associated with final NIHS score. Conclusions: In stroke patients without cardiovascular, cardiopulmonary and infectious diseases, serum pentraxin-3 levels are not associated with stroke prognosis. Highlights: Initial and final stroke volumes were associated with final NIHSS. Statistically significant difference were present between serum PTX-3 levels measured at the first and seventh day. PTX-3 was not associated with prognosis of acute non-cardiogenic ischemic stroke.